2003
DOI: 10.7164/antibiotics.56.783
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesterterpene, Sch 599473, from a Marine Sponge, Ircinia sp.

Abstract: mediates an essential event for antigen-specific T cell activation and an important mechanism for mounting an immune response.6) Thus, CCR7 could be a potential target for treatment of various metastases and/or inflammatory conditions.In this study, a fraction from a sponge was identified which showed inhibitory activity in the CCR7 receptor In the primary HTS assay, a sample in the MFL from a active fraction was subjected to further purification. The preliminary CG161 fractions were prepared as previously des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…342 Darwinella australensis collected from NW Australia contained sesterterpenoid sulfates 378-380 that inhibited the cell division of sea urchin eggs, but were not cytotoxic to human leukemia cells. 343 An Ircinia species collected at -70 m by dredging in the Gulf of Mexico contained a tricyclic sesterterpenoid, Sch 599473 381, 344 while the Antarctic sponge, Suberites caminatus yielded the rearranged sesterterpenoid aldehyde caminatal 382. 345 An asymmetric synthesis of (−)-cacospongionolide F, isolated from Fasciospongia cavernosa, 346 confirmed the original stereochemical assignments.…”
Section: Spongesmentioning
confidence: 99%
“…342 Darwinella australensis collected from NW Australia contained sesterterpenoid sulfates 378-380 that inhibited the cell division of sea urchin eggs, but were not cytotoxic to human leukemia cells. 343 An Ircinia species collected at -70 m by dredging in the Gulf of Mexico contained a tricyclic sesterterpenoid, Sch 599473 381, 344 while the Antarctic sponge, Suberites caminatus yielded the rearranged sesterterpenoid aldehyde caminatal 382. 345 An asymmetric synthesis of (−)-cacospongionolide F, isolated from Fasciospongia cavernosa, 346 confirmed the original stereochemical assignments.…”
Section: Spongesmentioning
confidence: 99%
“…With the purpose of contributing to the discovery of small molecule agonists and antagonists of chemokine receptors, Yang et al (Yang et al, 2003d), reported a new sesterterpene sulfircin (89) purified from the marine sponge Ircinia sp. that inhibited the CCR7 chemokine receptor, a receptor involved in the regulation of T cells and dendritic cell mobilization into lymphoid organs.…”
Section: Compounds Affecting the Immune Systemmentioning
confidence: 99%
“…90 An Ircinia species collected at −70 m by dredging in the Gulf of Mexico contained a sesterterpenoid 169. 91 Stoeba extensa (Japan) gave the cytotoxic halisulfate 7 165; 92 the C-8 stereochemistry of halisulfate 7, originally isolated from a Coscinoderma species, 89 has been revised to that shown as 170 on the basis of careful NOE analysis. 92 Two new sesterterpene sulfates, hipposulfates A 171 and B 172, have been isolated from an Okinawan sponge, Hippospongia cf.…”
Section: Bicarbocyclic Sesterterpenoidsmentioning
confidence: 99%